(untitled) (Research, Society and Development, 2022)
Information on hydrological behavior in hydrographic basins is essential for environmental diagnosis as well as for optimizing the use of water resources throughout the year. Thus, the objective of this study was to characterize the precipitation and flow in a southwest section of the Paraguaçu river basin, Bahia, Brazil. Pluviometric and fluviometric data referring to the historical series of the stations of João Amaro, Usina Mucugê, Andaraí and Iaçu were obtained through the portal of the National System of Information on Water Resources of the National Water Agency. For data processing, the Hidroweb software was used, which enabled the management of the databases. And Action Stat 3.6 software for statistical analysis. According to the results obtained, the average monthly rainfall totals are stationary and without deterministic seasonality in the entire historical series. December was the rainiest for both the Chapada area and the Iaçu area. The probabilities of flows occurring permanently throughout the year in Iaçu are highly significant.